2012
DOI: 10.2298/aci1203113r
|View full text |Cite
|
Sign up to set email alerts
|

The selection of best anesthesiological technique for hip fracture surgery in older high-risk patients

Abstract: Peripheral nerve blocks are safe and effective anesthesiological technique, which may reduce the mortality in patients with the hip fracture and maintain the hemodynamic stability, both during and after the surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Several studies demonstrated that compared with general anesthesia, neuraxial anesthesia has some advantages such as airway management avoidance, no intubation requirement, and prolonged postoperative analgesia [4]. Furthermore, neuraxial anesthesia could decrease blood loss, potentially reduce risk of postoperative nausea and vomitting (PONV), as well as deep venous thrombosis [4][5][6]. Conversely, general anesthesia is reported to provide a more stable hemodynamic state, faster induction, and avoid some complications such as pneumonia, epidural haematoma and infection [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that compared with general anesthesia, neuraxial anesthesia has some advantages such as airway management avoidance, no intubation requirement, and prolonged postoperative analgesia [4]. Furthermore, neuraxial anesthesia could decrease blood loss, potentially reduce risk of postoperative nausea and vomitting (PONV), as well as deep venous thrombosis [4][5][6]. Conversely, general anesthesia is reported to provide a more stable hemodynamic state, faster induction, and avoid some complications such as pneumonia, epidural haematoma and infection [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that compared with general anesthesia, neuraxial anesthesia has some advantages such as airway management avoidance, no intubation requirement, and prolonged postoperative analgesia 4 . Furthermore, neuraxial anesthesia could provide excellent intraoperative anesthesia, decrease blood loss, potentially reduce risk of postoperative nausea and vomitting (PONV), as well as deep venous thrombosis [4][5][6] . Conversely, general anesthesia is reported to provide a more stable hemodynamic state, faster induction, and avoid some complications such as pneumonia, epidural haematoma and infection 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that compared with general anesthesia, neuraxial anesthesia has some advantages such as airway management avoidance, no intubation requirement, and prolonged postoperative analgesia 4 . Furthermore, neuraxial anesthesia could provide excellent intraoperative anesthesia, decrease blood loss, potentially reduce risk of postoperative nausea and vomitting (PONV), as well as deep venous thrombosis [4][5][6] . Conversely, general anesthesia is reported to provide a more stable hemodynamic state, faster induction, and avoid some complications such as pneumonia, epidural haematoma and infection 7,8 .…”
Section: Introductionmentioning
confidence: 99%